Earth 2100 - ABC News (USA ABC News, 2009)
Its an idea that most of us would rather not think about-that within the next century, life as we know it could come to an end. Our civilization could crumble, leaving only traces of modern human existence behind it. It seems outlandish, extreme, even impossible. But according to cutting edge scientific research, it is a real possibility unless we make drastic changes now. Experts say that over the next 100 years the "perfect storm" of population growth, resource depletion and climate change could converge with catastrophic results. Hosted by Bob Woodruff, Earth 2100 takes viewers on a virtual journey through the next century to find out what may lie ahead and what might be done to avoid disaster.
Runs for 84 minutes
Keywords: Climate Change, Population growth Natural resource depletion